Developing Culture-based English Learning at the Ninth Grade Student in UPTD SMP Negeri 2 Gunungsitoli in 2024/2025: English - Deary Alfanny Zendrato; Elwin P. Zebua; Nursayani Maru’ao; Afore T. Harefa (Prodi Tadris Bahasa Inggris, 2025)
This study aims to develop culture-based English learning in the 9th-grade students of UPTD SMP Negeri 2 Gunungsitoli Alo'oa by using a research amd development method. The development process is based on the Borg and Gall development research model, simplified into three stages: a) Preliminary Study, b) Product Development, and c) Finalization and testing of the product that integrates local cultural aspects. Data were collected through observations, interviews, and questionnaires for developing teaching materials to measure the effectiveness of the learning process. The results indicate that the integration of local cultural elements in English learning is enhances student motivation, enriches their understanding of language and culture, recognize the significance of cultural context in their language acquisition and develops a framework integrating local cultural elements into English language that connected to the local cultural contexts lesson that affected their understanding and application of the language. This research recommends applying similar methods in other schools to enhance contextual and relevant English learning.